Variations in the Neurosurgical Management of Depressed Skull Fractures in Adults: An International Cross-Sectional Survey - Suliman, Amir; Jayakumar, Nithish; Chaurasia, Bipin; Holliman, Damian (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2023)
Background Depressed skull fractures have been well described since antiquity, yet its management remains controversial. Contentious issues include the use of prophylactic antibiotics and antiepileptics, the role of nonoperative management, and the replacement/removal of bone fragments. Our objective was to explore the management patterns of closed and open depressed skull fractures across the world.Methods A 23-item, web-based survey was distributed electronically to the members of national neurosurgical associations, and on social media platforms. The survey was open for data collection from December 2020 to April 2021.Results A total of 218 respondents completed the survey, representing 56 countries.With regard to open fractures, most respondents (85.8%) treated less than 50 cases annually. Most respondents (79.4%) offered prophylactic antibiotics to all patients with open fractures, with significant geographical variation (p < 0.001). Less than half of the respondents (48.2%) offered prophylactic antiepileptics. Almost all respondents (>90%) reported the following indications as important for surgical management: (1) grossly contaminated wound, (2) dural penetration, (3) depth of depression, and (4) underlying contusion/hematoma with mass effect. Most respondents treated less than 50 cases of closed depressed skull fractures annually. Most European respondents (81.7%) did not offer prophylactic antiepileptics in comparison to most Asian respondents (52.7%; p < 0.001). Depth of depression, an underlying hematoma/contusion with mass effect, and dural penetration were the most important surgical indications.Conclusions There remains a great degree of uncertainty in the management strategies employed across the world in treating depressed fractures, and future work should involve multinational randomized trials.
Keywords: depressed skull fractures; compound depressed skull fractures; traumatic brain injury; online survey; cross-sectional study